2011
DOI: 10.1007/978-3-642-18336-2_66
|View full text |Cite
|
Sign up to set email alerts
|

Soil Erosion Features by Land Use and Land Cover in Hilly Agricultural Watersheds in Central Sichuan Province, China

Abstract: Abstract. The study assessed soil erosion features in hilly agricultural watersheds in central Sichuan Province, China. Relationships among area percentages of land covers, soil erosion modulus, soil loss rate, and area percentage of erosion in the watersheds were examined by multivariate regression analysis. The first two regression models were constructed with area percentages of land covers as independent variables and soil erosion modulus or soil loss rate as dependent variables. The third one was built wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A comparison of the soil erosion generated by different land use/land covers indicates that there is a significant reduction in the amount of soil erosion when there is a change from arable land to semi-natural vegetation and to forests [6,[9][10][11]. For example, Borrelli et al [6] indicated that transforming forest land covers to another land use/to other land covers can potentially increase soil erosion by 0.61 billion tons yr −1 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison of the soil erosion generated by different land use/land covers indicates that there is a significant reduction in the amount of soil erosion when there is a change from arable land to semi-natural vegetation and to forests [6,[9][10][11]. For example, Borrelli et al [6] indicated that transforming forest land covers to another land use/to other land covers can potentially increase soil erosion by 0.61 billion tons yr −1 .…”
Section: Introductionmentioning
confidence: 99%
“…The rate of soil erosion in orchards (23.52 t ha −1 yr −1 ), in grasslands (0.3-3.62 t ha −1 yr −1 ), and in shrublands (0.3-1.57 t ha −1 yr −1 ), fall between the rates for bare lands and for forests, and can be arranged in descending order. Forest cover, both natural and artificial, is one of the most important land covers for providing protection against soil erosion [6,9,10,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation